2021
DOI: 10.3390/ijerph18157764
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Longitudinal Relationship between Executive Dysfunction and Happiness in Korean Children

Abstract: The goal of this study was to examine the reciprocal longitudinal relationships between executive dysfunction and happiness for Korean children. We used data from the Panel Study of Korean Children (PSKC) conducted by the Korean Institute of Child Care and Education. A total of 1240 valid responses from the first to third grade in elementary school were analyzed using autoregressive crossed-lagged modeling. As a result, executive dysfunction and happiness were found to have reciprocal influences over the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In a follow-up study, it is necessary to reveal how EFD transitions over time and what factors affect the transition through latent transition analysis. Variables that predict or correlate with EF or EFD identified in previous studies have been reported in various areas: child-related ( Jacobsen et al 2017 ; Sung and Choi 2021 ; Tillman et al 2015 ; Wang and Zhou 2019 ), parent-related ( Altenburger and Schoppe-Sullivan 2021 ; De Cock et al 2017 ; Gustafsson et al 2015 ; Hughes et al 2013 ; Lucassen et al 2015 ; Meuwissen and Englund 2016 ), and home-related ( Last et al 2018 ; Sarsour et al 2011 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a follow-up study, it is necessary to reveal how EFD transitions over time and what factors affect the transition through latent transition analysis. Variables that predict or correlate with EF or EFD identified in previous studies have been reported in various areas: child-related ( Jacobsen et al 2017 ; Sung and Choi 2021 ; Tillman et al 2015 ; Wang and Zhou 2019 ), parent-related ( Altenburger and Schoppe-Sullivan 2021 ; De Cock et al 2017 ; Gustafsson et al 2015 ; Hughes et al 2013 ; Lucassen et al 2015 ; Meuwissen and Englund 2016 ), and home-related ( Last et al 2018 ; Sarsour et al 2011 ).…”
Section: Discussionmentioning
confidence: 92%
“…In our study, children’s happiness and home environment factors were also major predictors. It has been reported that positive psychological factors, such as children’s self-esteem ( Bajaj et al 2016 ; He et al 2021 ) and happiness ( Choi and Choi 2019 ; Sung and Choi 2021 ) also affect the development of children’s EF. In addition, a rich home environment is favorable to children’s EF ( Dilworth-Bart et al 2007 ; Sarsour et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child happiness was assessed using six items of a child self-report from an instrument developed previously [54] and then translated and revised by the PSKC for better understanding [55]. A survey researcher conducted in-person visits to the participants' households.…”
Section: Child Happinessmentioning
confidence: 99%
“…EF plays a role in many aspects of one’s life, including academic success and physical and mental health. Better EF abilities have been linked to higher happiness ( Sung and Choi, 2021 ), health behaviors ( Hall et al, 2008 ; Allan et al, 2016 ), emotional regulation ( Groves et al, 2021 ), mind-wandering ( Kane et al, 2007 ; Unsworth and Robison, 2016 ), resilience ( Zhang et al, 2019 ), academic achievement ( Ahmed et al, 2019 ), and social competence ( Fong and Iarocci, 2020 ). Therefore, there has been evidence that higher EF abilities relate to higher well-being in youth.…”
Section: Introductionmentioning
confidence: 99%